THE CANTERAS-GALIFA NEOGENE CONGLOMERATES: EVIDENCE FOR AN OPHIOLITIC ASSOCIATION SUBMERGED IN THE MEDITERRANEAN SEA AT THE EASTERN END OF THE BETIC CHAIN - Puga, Encarnación; Díaz de Federico, Antonio; Manteca Martínez, José Ignacio; Rodríguez Martínez-Conde, José Angel; Díaz Puga, Miguel Angel (Ofioliti, 2004)
The conglomerates studied here from a petrological and geochemical point of view constitute a formation of deltaic origin dating to the late Tortonian, which is very well represented in all the Neogene inter-mountain basins of the Betic Cordillera. The most abundant blocks in the formation are metamorphic rocks deriving from the Nevado - Filábride domain in the central and eastern zones of the Betic Cordillera. These blocks can be up to several cubic metres in size, particularly in the southern area of the basin. The most common rock types found amongst the blocks are: amphibolites, eclogites, serpentinites, quartzites, calc-schists and micaschists, all similar to those forming the ophiolitic association of the Mulhacén Complex in the central and western zones of the Nevado - Filábride domain. The chemical and mineralogical composition of the metabasite blocks indicates that their protoliths developed from a basic magma generated in an ocean-ridge tectonic setting and that some of them underwent ocean-floor metamorphism before the Alpine orogeny. The serpentinite blocks have undergone chemical changes that indicate a metasomatic process in an ocean environment similar to that which generated rodingites in the ophiolitic outcrops. Both the basic and ultramafic igneous blocks and those of sedimentary origin show an overlapping of partly obliterated metamorphic facies, suggesting the development of a primary metamorphic event under eclogite-facies conditions, followed by another under albite-epidote amphibolite to greenschist- facies conditions. The lithology of these blocks together with their geochemistry and metamorphic evolution lead to the conclusion that they derive from an ophiolitic association similar to that previously identified in the central and western zones of the Mulhacén Complex. On the basis of stratigraphic criteria, the ophiolitic source area should lie to the south of the Neogene basin where the Canteras - Galifa conglomerates were deposited. This area, however, does not crop out at present, probably owing to tectonic sinking of the ophiolitic formation below the Mediterranean sea level after a late Tortonian exhumation stage during which the blocks were formed.